Fraction distribution and migration of heavy metals in mangrove-sediment system under sulphur and phosphorus amendment. Issue 1 (2nd January 2016) - Li, Jian; Liu, Jingchun; Lin, Yushan; Yan, Chongling; Lu, Haoliang
ABSTRACT: In this study, mangrove seedlings ( Kandelia obovata (S. L.)) were cultivated in rhizo-boxes, which contain sediments collected from natural mangrove forest and modified with different rates of sulphate and phosphate. The fraction distributions of Zn, Cd, Cu, Ni and Pb in rhizosphere and non-rhizosphere sediments were studied by using a sequential extraction method. Metal concentrations in plant tissues and iron plaque on root surface were also determined to reveal migration variation of heavy metals in the plant-sediment system. The results showed that the activities of K. obovata roots enhance the reducible metals while reducing acid-extractable and oxidisable metals; sulphur amendment benefits the combination of metal ions with S 2– and therefore reduces the bioavailability of metal pollutants; addition of sulphur also improves the content of iron plaque on the root surface, which plays an important role in metal accumulation by K. obovata root tissue; the addition of sulphur markedly reduces the concentration of Cd in roots, but significantly enhanced the concentrations of Cu, Zn, Ni and Pb in roots. The results indicate that sulphur and phosphorus content in mangrove sediment, and the growth of mangrove plant can significantly influence the migration of heavy metals in the mangrove wetland ecosystem.